Rede de Bibliotecas da Amazônia ( REBAM ): da gênese ao desaparecimento - Maria Cristina Guimaraes Loureiro (1986)
The study of the Amazônia Library Network (Rebam) has been fulfilled through the institutional analysis , as a method of documental analysis ( which provides condition to visualize the social contradictions in the organizational process ) , in conjunction with the structuralism (amethod which studies the interrelations of the organizational parts of a network) . Rebam was founded in 1973 in the " Amazônia Legal " inordertogive support to the Brazilian National System of Scientific and Technological Information (Snict ) . Its purpose was the storage and dissemination of information produced about Amazônia and by amazonian organizations . The network was constituted by 12 institution s , under the coordination of the Superintendência do Desenvolvimento da Amazônia (Sudam) .However Rebam did not survive for a long time and the main reasons were : the lack of maturity and technical preparation of its librarians: institutional and personal disagreement on both technical and political matters ; lack of financial commitment from member organizations ; and institutional preponderance of Suda mover the network .